Os sentidos da interdisciplinaridade no trabalho em saúde mental - Giacomini, Eduardo (2022)
Interdisciplinarity is the center of reflections that come from different areas of knowledge, either as a methodological resource for scientific research, or as a concrete work strategy. In the health area, interdisciplinary actions appear as a counter-hegemonic attitude, aimed at overcoming solitary, fragmented and excessively specialized professional postures directed at biological and individual bodies. Issues related to mental health and what is supposed to be psychic illness are growing in the world, revealing the failure of the biomedical health model to control the problem. This research aimed to analyze the expression of interdisciplinarity in mental health care practices. This is an exploratory study with a qualitative approach, in which two methodological procedures were combined: an integrative literature review and; an exploratory phase represented by non-directed interviews. The integrative literature review took place between May and August 2021, with searches in the BVS, SciELO, Scopus, Google Scholar, OpenGrey and ProQuest databases, in Portuguese, English, Spanish, French and Italian, and resulted in the selection of 43 productions, which were reported and examined in the light of the theoretical framework of collective health, with thematic content analysis technique. Between June and December 2021, 5 non-directed interviews were carried out with people who, for at least ten years, had been involved in studies or debates about mental health work, and who expressed a theoretical approach to the area of collective health. Data from more than 330 minutes of narratives, produced in the interviews, were subjected to content analysis, of the thematic type. Among the studies selected in the integrative literature review, there was a predominance of Brazilian studies, dating from the last ten years, coming from the health area and developed under a qualitative approach. In the bibliographic sample, 54 excerpts aimed at characterizing interdisciplinary work were recovered, whose analysis allowed the recognition of four thematic categories linked to interdisciplinarity in the context of mental health care practices: concept, operationality, objective and attributes. The sample of interviewees was composed of 3 women and 2 men, of whom 4 were graduated in medicine and 1 in nursing, 4 had a doctoral degree and 1 a post-doctoral degree, and all of them performed teaching activities in undergraduate, graduate or both. The time of involvement in studies or debates about mental health work ranged from 15 to more than 40 years. Based on the analysis of the interviews, four thematic categories were identified: concept of interdisciplinarity in mental health work, operationalization of interdisciplinary work in mental health, possibilities and limits for carrying out interdisciplinary work in mental health and the relationship between collective health and interdisciplinary work in mental health. Final considerations: it was found, with this study, the existence of a theoretical gap regarding what characterizes interdisciplinarity in mental health carepractices; the concept of interdisciplinarity is dynamic and not delimitable, but subject to some theoretical demarcations; interdisciplinarity represents an opportunity to overcome the biomedical model of care; it is expressed in the concrete plan of work in mental health; lack of diverse professionals with skills to relate knowledge; it is influenced by management models and the disciplinary paradigm; it is capable of producing new practices; training for interdisciplinary work is necessary for its occurrence and; practices and debates that relate interdisciplinarity and mental health care find fruitful space in the field of collective health.